The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1044/2014_jslhr-h-14-0013
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Medial Olivocochlear Reflex as Measured by Distortion Product Otoacoustic Emissions

Abstract: Purpose: The purpose of this study was to assess the repeatability of a fine-resolution, distortion product otoacoustic emission (DPOAE)-based assay of the medial olivocochlear (MOC) reflex in normal-hearing adults. Method: Data were collected during 36 test sessions from 4 normal-hearing adults to assess short-term stability and 5 normal-hearing adults to assess long-term stability. DPOAE level and phase measurements were recorded with and without contralateral acoustic stimulation. MOC reflex indices were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 53 publications
2
26
1
Order By: Relevance
“…Many of the researchers have measured MOCB activity using contralateral inhibition of click evoked or transient evoked otoacoustic emissions (TEOAEs) [ 6 - 8 , 10 ] and contralateral acoustic stimulation (CAS) has shown to reduce the amplitude of transient evoked otoacoustic emissions for various types of noise [ 11 ]. The effects of CAS on the DPOAE has been reported by several investigators [ 5 , 12 - 15 ] and findings of these investigations have reported both reduction and enhancement of amplitude of DPOAEs [ 12 , 13 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Many of the researchers have measured MOCB activity using contralateral inhibition of click evoked or transient evoked otoacoustic emissions (TEOAEs) [ 6 - 8 , 10 ] and contralateral acoustic stimulation (CAS) has shown to reduce the amplitude of transient evoked otoacoustic emissions for various types of noise [ 11 ]. The effects of CAS on the DPOAE has been reported by several investigators [ 5 , 12 - 15 ] and findings of these investigations have reported both reduction and enhancement of amplitude of DPOAEs [ 12 , 13 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 96%
“…When the DPOAEs are measured in ear canal, the constructive and destructive interferences between the two components of DPOAE results in peaks and dips in the response amplitude as a function of frequency. This oscillation in DPOAE phase and level is referred to as DPOAE fine structure [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since reflection source emissions are generated near the peak of the traveling wave, OAEs recorded at low levels are sensitive to subtle cochlear amplifier gain changes (Shera, 2004). For example, medial efferent activation by contralateral acoustic stimulation produces larger changes in the reflection-compared to the distortion-component of distortion product OAEs (Abdala et al, 2009;Mishra and Abdala, 2015). Additionally, reflection-source OAE delays, including CEOAE latencies, can be applied to objectively estimate cochlear tuning in humans and other animals (Bentsen et al, 2011;Bergevin et al, 2012;Joris et al, 2011;Keefe, 2012;Moleti et al, 2008;Shera et al, 2002;Sisto and Moleti, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…For instance, CEOAE latency can be used to objectively estimate cochlear tuning in the pediatric population, in whom psychophysical tuning curves may be difficult to obtain (Moleti and Sisto, 2003;Moleti et al, 2008). The latency can be applied to accurately characterize the efferent effects on cochlear mechanisms (Francis and Guinan, 2010) and compute a vector metric to index efferent reflex (Abdala et al, 2013;Marshall et al, 2014;Mishra and Abdala, 2015).…”
Section: Introductionmentioning
confidence: 99%